New paradigm approach on preventive health care management: User perspective - Kang, Eng Thye (Institute Kajian Pengguna, Universiti Utara Malaysia, 2001)
Health problem is the biggest challenge in this new century as reported by most medical practitioner and scientist. This problem has reached the stage of "crises" as commented by the medical expert. On the other hand, all kinds of research effort on drugs, medical technology especially however still seem not able to overcome the disease effectively. In Malaysia, the statistical report of 1 of 20 person with diabetes on 1990 increase to 1 of 10 person in 2000 has shown the seriousness of health status of Malaysian citizen. This figure however did not yet include the diseases such as high blood pressure, cancer, heart attack, etc. According to the WHO and ILO, estimated 1 million workers die work reIated deaths each year and hundreds of millions more are harmed by their job as reported by Rory O'Neill. Levine (2000) reported that 4% of world GDP lost to workrelated injuries, illness and death and the cost of occupational injuries in developing countries about 10% of GDP. He added any country could reduce this figure by half, they could easily pay off foreign debt. Therefore, as part of the effort to solve this terrible health crisis, the purpose of this paper is an attempt to introduce and present the new paradigm of Health Care Management Concept to industries in order to overcome the occupational diseases faced by most employees through a more well organized preventive health care approach.